Integrating mHealth and Systems Science: A Combination Approach to Prevent and Treat Chronic Health Conditions - Oreskovic, Nicolas Michel; Huang, Terry T; Moon, Jon (JMIR Publications, 2015)
Chronic health conditions are a growing global health concern and account for over half of all deaths worldwide. Finding ways to decrease the burden of and resources allotted to chronic health conditions is of primary importance. Recent advances in technology and insights into modeling techniques offer promising approaches, which if combined, represent a novel direction that would further advance the prevention and treatment of chronic health conditions.